2012
DOI: 10.1007/s13224-012-0222-0
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia in Pregnancy: Intravenous Versus Oral Route

Abstract: Objectives The aim of this study was to compare the efficacy and safety of intravenous iron with oral iron in the treatment of iron deficiency anemia of pregnancy. Methods A randomized experimental study was conducted at K. J. Somaiya Hospital involving 200 pregnant women with iron deficiency anemia. In the intravenous group iron dose was calculated from: Total iron dose required (mg) = 2.4 9 weight kg 9 target hemoglobinactual hemoglobin) g/dl ? 500. Target hemoglobin was set at 12 g/dl. In the oral group pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 9 publications
2
71
0
Order By: Relevance
“…The majority of studies involved a comparison group of some kind including oral iron (n = 17; 36%), 11,14,16,19,24,26,27,29,31,32,34,35,37,39,50,56,57 IV iron (n = 4; 9%), 13 [14][15][16]18,20,24,26,28,31,[33][34][35][36][37][38][39]41,42,44,49,50,53 Only one study was identified that directly compared the administration of a full replacement dose of IV iron to a dose that was 300 mg less than the calculated full replacement dose. In comparing the two groups, administration of the full replacement dose was associated with a greater increase of 8 g/L 3-4 weeks after administration and 14 g/L at delivery.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The majority of studies involved a comparison group of some kind including oral iron (n = 17; 36%), 11,14,16,19,24,26,27,29,31,32,34,35,37,39,50,56,57 IV iron (n = 4; 9%), 13 [14][15][16]18,20,24,26,28,31,[33][34][35][36][37][38][39]41,42,44,49,50,53 Only one study was identified that directly compared the administration of a full replacement dose of IV iron to a dose that was 300 mg less than the calculated full replacement dose. In comparing the two groups, administration of the full replacement dose was associated with a greater increase of 8 g/L 3-4 weeks after administration and 14 g/L at delivery.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…14,16,29,32,34,35,39,50,56 Two studies compared IV to IM administration, noting a higher rate of ADRs in the IM group (27% and 24%) compared with the IV group (3% and 8%).…”
Section: Tolerabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies [15][16][17][18][19] have compared efficacy and safety of intravenous iron sucrose with oral iron during pregnancy. A recent Cochrane review 20 on treatments for iron deficiency in anemia highlighted the need for good quality randomized controlled trials in this setting, in particular to assess clinical outcomes and adverse events.…”
Section: Introductionmentioning
confidence: 99%